Lighting Device with Variable Spectral Composition for Growing "Chlorella" in Artificial Conditions; Key Engineering Materials; Vol. 712 : Advanced Materials for Technical and Medical Purpose (AMTMP 2016) - Turanov S. B. Sergey Borisovich (Materials and Technologies for Biomedical Application and Environmental Engineering, 2016)
Title screen